Adult coeliac disease and sarcoidosis: a rare association - Maia, Carla (2001)
The authors report the case of a 31-year-old womanwith a paucisymptomatic form of adult coeliacdisease, diagnosed in May 95, based essentially onlaboratory findings (ferropenic anaemia, low serumfolate, positive antigliadin and endomysialantibodies) and histopathological grounds (subtotalvillous atrophy). Improvement was seen followingadherence to a gluten-free diet.In May 98 the patient presented with sudden onsetof fever. Oligoarthritis and erythema nodosumdeveloped; bilateral hilar lymphadenopathy wasfound, symptoms and signs typical of acutesarcoidosis – Löfgren syndrome. The diagnosis wassupported by bronchoalveolar lavage and lymphnode histology. Other systemic disorders with asimilar presentation were excluded.Several autoimmune diseases have been associated with coeliac disease, such as thyroid disorders,Addison’s disease, primary biliary cirrhosis, IgAnephropathy and insulin-dependent diabetesmellitus. The association between sarcoidosis andcoeliac disease has been rarely described in theliterature (only ten cases to date).The immunological mechanisms, accepted asresponsible for this association, are discussed